Evaluation of freight forwarder risk to transportation market entry - Naumov, Vitalii (Eastern-European Journal of Enterprise Technologies, 2015)
Consideration of risks in managing freight forwarding processes allows decreasing potential losses as the result of market situation change for logistics system elements, which are involved in delivery process. Existing approaches to freight forwarders risks estimation are usually not based on technological process model; they take into consideration external factors, such as legal framework, traffic conditions, logistics system structure and others. In the paper in order to evaluate freight forwarder risk to entry the transportation market, a simulation model of servicing by the forwarding company of requests flow has been developed. Regression model, obtained on the basis of simulation results, allows to estimate numerically a measure of freight forwarder risk without the simulations of the process of requests servicing. Provided results of research allow to state, that forwarding company risk to entry the market monotonically increases with increasing of average requests interval in the serviced flow and monotonically decreases with increasing of the tariff on services of a freight forwarder. Research results should be considered while managing the process of freight forwarders entry to new markets.